Juridical Analysis of Violation of Core-Plasma Partnership Agreement of Palm Oil Plantation Between PT Hardaya Inti Plantation and Plasma Amanah Farmers Cooperative (Case Study of KPPU Decision No. 02/KPPU-K/2023) - Syarief Hidayatullah; Surahman Surahman; Muhammad Nurcholis Alhadi; Elviandri Elviandri (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The inti-plasma partnership scheme in the oil palm plantation sector aims to create a mutually beneficial relationship between large companies (nucleus) and smallholders (plasma). However, in practice, there are often inequalities that cause plasma farmers to lose control over their businesses. This research analyzes the violation of the partnership agreement between PT Hardaya Inti Plantations (PT HIP) and Koperasi Tani Plasma Amanah as decided in KPPU Decision No. 02/KPPU-K/2023. The focus of the analysis includes the forms of juridical, financial, and operational control that PT HIP exercised over the cooperative, as well as the legal implications based on Jeremy Bentham's theories of civil law, competition, and justice. The results show that PT HIP has abused its dominant position by fully controlling the partnership agreement, limiting cooperatives' access to decision-making, and implementing non-transparent financial practices. KPPU has imposed administrative sanctions in the form of an agreement addendum obligation, an independent audit, and a fine of Rp1,000,000,000.00. However, an evaluation of this decision indicates that the sanction has not fully provided substantive justice for plasma farmers, given the absence of a direct compensation mechanism. Therefore, there is a need to strengthen regulations and implement more effective monitoring and law enforcement mechanisms to ensure fairer and more sustainable partnership relationships in the oil palm plantation industry in Indonesia.